Measuring MPAs in Continental North America: How Well Protected Are the Ocean Estates of Canada, Mexico, and the USA? - Jessen, Sabine; Morgan, Lance E.; Bezaury-Creel, Juan E.; Barron, Alexandra; Govender, Rhona; Pike, Elizabeth P.; Saccomanno, Vienna R.; Moffitt, Russell A. (Frontiers in Marine Science, 2017)
Marine protected areas (MPAs) are a well-established conservation strategy, employed around the world to protect important marine species and ecosystems and support the recovery of declining populations. The continental waters of North America contain remarkable biodiversity, but many species face increasing pressure from overexploitation, climate change, and other anthropogenic impacts. Canada, Mexico, and the USA have pledged to protect at least 10% of their marine and coastal waters by 2020 as signatories to the Convention on Biological Diversity, and have made efforts to establish MPAs. These MPAs vary widely in terms of levels of protection and designation processes; information that is not reflected in official statistics. To this end, we critically examined progress towards the CBD target for marine protection in continental North American waters to determine how well ocean ecosystems are protected by MPAs. We reviewed government data to determine whether MPAs met four criteria: legal designation, permanence, presence of an administrative structure, and a completed management plan. Sites that met all four criteria were categorized as “implemented”. Any sites that failed to meet one or more criterion were considered “incompletely implemented” and excluded from the analysis. We also calculated the amount of “fully-protected” MPAs in which all extractive uses are prohibited. We found that less than 1% of North America’s continental ocean is protected, and only 0.04% is fully-protected. Canada has the least area protected with just 0.11% in implemented MPAs, and 0.01% in fully-protected MPAs. Mexico and the USA have 1.62 and 1.29% in implemented MPAs, and 0.11 and 0.03% in fully-protected MPAs, respectively. Results show that many North American MPAs are incompletely implemented and therefore currently fail to provide adequate protection. The inclusion of such sites in official government statistics can inflate the perception of how much, and how well, the ocean is protected. We outline some of the major challenges to MPA establishment in each country and offer recommendations to increase the number and effectiveness of MPAs in North America.